Nickel-based catalyst as well as preparation method and application thereof
By loading nickel oxide and other metal oxides on a nickel-based catalyst, the problems of low phenylacetylene hydrogenation rate and high styrene loss rate are solved, and efficient selective hydrogenation of phenylacetylene at low temperature is achieved, which is suitable for the hydrogenation of phenylacetylene in the C8 fraction.
Patent Information
- Application Number
- CN202410449946.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-15
- Publication Date
- 2025-10-21
AI Technical Summary
In the prior art, during the selective hydrogenation of phenylacetylene in a styrene-rich C8 fraction, the phenylacetylene hydrogenation rate is low and the styrene loss rate is high.
A nickel-based catalyst is used, by loading nickel oxide on a carrier and combining aluminum oxide, molybdenum oxide, lithium and potassium as well as phosphorus oxide and fluorine to optimize the acidity and specific surface area, and thus prepare a catalyst with high activity and low styrene loss rate.
It achieves high phenylacetylene hydrogenation rate and low styrene loss rate under low temperature conditions, and is suitable for the selective hydrogenation of phenylacetylene in the styrene-rich C8 fraction, with good selectivity and stability.
Smart Images

Figure BDA0004792282690000041 
Figure BDA0004792282690000131 
Figure BDA0004792282690000141
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and more particularly to a nickel-based catalyst, a preparation method thereof, and an application thereof. Background Art
[0002] Styrene (ST) is a key monomer in the production of polystyrene (PS), ABS resin, and styrene-butadiene rubber. Currently, the main methods for producing styrene worldwide include ethylbenzene dehydrogenation, propylene oxide-styrene (PO / SM) co-production, and pyrolysis gasoline extraction and distillation recovery. EBDH accounts for approximately 90% of the world's total styrene production capacity and is the primary method for producing styrene both domestically and internationally. However, in recent years, with the expansion of ethylene production, particularly the commissioning of million-ton-scale ethylene plants, styrene extraction and recovery from pyrolysis gasoline has become a highly sought-after technology for increasing styrene production.
[0003] Pyrolysis gasoline is a significant byproduct of the ethylene industry, accounting for approximately 60-70% of ethylene production capacity and containing approximately 4-6% styrene. Traditionally, the C6-C8 fraction of pyrolysis gasoline undergoes a two-stage hydrogenation process, where the styrene is saturated into ethylbenzene, which is then used along with xylenes as a gasoline blending component or as a feedstock for C8 aromatics isomerization. The ratio of ethylbenzene to xylene isomers in hydrogenated pyrolysis gasoline is approximately 1:1. This high ethylbenzene content reduces its value as a feedstock for xylene production plants, impacts the processing capacity of paraxylene production plants, and increases the recycle volume in the xylene isomerization loop.
[0004] For large-scale ethylene plants, separating styrene before hydrogenating pyrolysis gasoline offers significant economic benefits: ① Styrene with a purity greater than 99.7% can be separated, upgrading its value from fuel to chemical. Mixed xylenes can be recovered and used to produce isomers like paraxylene, upgrading the xylene fraction from fuel to chemical value. For example, a 1 million ton / year ethylene plant could cost-effectively produce 2.4 to 4.2 kt / yr of styrene. ② The plant's hydrogenation load can be significantly reduced, lowering hydrogen consumption. ③ The production cost is half that of ethylbenzene dehydrogenation.
[0005] Extractive distillation is commonly used to recover styrene from pyrolysis gasoline. Due to the similar chemical structure of phenylacetylene (PA) and styrene, and their interactions with the extractant, extractive distillation cannot effectively separate styrene from PA. The phenylacetylene must first be selectively hydrogenated to remove it before styrene extraction. PA is also a poison in styrene block copolymerization reactions, increasing catalyst consumption during styrene anionic polymerization, hindering chain growth and polymerization, and causing deterioration of polystyrene properties, such as discoloration, degradation, taste changes, and odor release. Therefore, the development of highly selective phenylacetylene selective hydrogenation catalysts has become a core technology for recovering styrene from pyrolysis gasoline. Furthermore, minimizing styrene loss is crucial to the competitiveness of styrene recovery from pyrolysis gasoline.
[0006] Chinese patent CN1298376A discloses a method for hydrogenating phenylacetylene in a styrene-containing medium using a catalyst. The method employs a supported nickel catalyst having a nickel content of 10 to 25 wt% and a bubbling bed reactor to hydrogenate phenylacetylene in a styrene-containing medium. However, the patent only describes the selective hydrogenation of phenylacetylene from the perspective of process control. However, the catalyst's hydrogenation performance is unsatisfactory under highly demanding process conditions. Furthermore, the loss of styrene during the process is not described in detail.
[0007] Chinese Patent CN1087892A describes a hydrogenation method and apparatus for purifying phenylacetylene from a styrene stream. The method involves adding hydrogen to a diluent, such as nitrogen, to dilute the hydrogen, mixing the hydrogen with a catalyst selectivity improver, such as carbon monoxide, using ethylbenzene dehydrogenation exhaust gas to provide hydrogen, and hydrogenating the phenylacetylene impurity to styrene using a multi-stage catalytic reactor. However, the patent only describes a selective hydrogenation and deacetylation process for low phenylacetylene concentrations, such as 300 ppm. Furthermore, the phenylacetylene hydrogenation rate is low (approximately 95%), and the styrene loss rate is approximately 0.2%. This method only includes minor process improvements and does not elaborate on the catalyst.
[0008] Chinese patent CN1852877A discloses a method for hydrogenating phenylacetylene impurities in the presence of styrene monomer. A styrene monomer stream containing a small amount of phenylacetylene and a hydrogenation gas containing hydrogen are supplied to a hydrogenation reactor. The styrene monomer stream and hydrogen are contacted with a bed containing a catalyst comprising a reduced copper compound on a θ-alumina support. The hydrogenation reaction is operated at a temperature of at least 60°C and a pressure of at least 30 psig to hydrogenate the phenylacetylene to produce styrene. The hydrogenation gas is a mixture of nitrogen and hydrogen. The catalyst reacts at a relatively high reaction temperature, resulting in a low phenylacetylene hydrogenation rate of approximately 70%. Furthermore, the catalyst has a short catalyst life and a high styrene loss rate (approximately 3%).
[0009] Chinese patent CN101475438A discloses a method for the selective hydrogenation of phenylacetylene in the presence of styrene. Using carbon-containing nickel or palladium oxide as a catalyst, a hydrocarbon material containing phenylacetylene and hydrogen are brought into contact with the catalyst in a reactor, hydrogenating the phenylacetylene to styrene. However, this method requires pre-coking the catalyst at a certain temperature, making it unsuitable for practical application.
[0010] Therefore, how to improve the phenylacetylene hydrogenation rate in the selective hydrogenation process of phenylacetylene in the presence of styrene and simultaneously reduce the loss rate of styrene is a technical problem that needs to be solved urgently. Summary of the Invention
[0011] The object of the present invention is to provide a nickel-based catalyst, a preparation method and an application thereof, so as to solve the technical problems in the prior art of low phenylacetylene hydrogenation rate and high styrene loss rate in the selective hydrogenation of phenylacetylene in a styrene-rich C8 fraction.
[0012] To achieve the above object, the technical solution adopted by the present invention is:
[0013] In a first aspect, the present invention provides a nickel-based catalyst comprising a carrier and nickel oxide supported on the carrier, wherein the carrier comprises aluminum oxide, molybdenum oxide, at least one metal oxide of lithium and potassium, and at least one of phosphorus oxide and fluorine.
[0014] The content of each component in the nickel-based catalyst is as follows:
[0015]
[0016] The balance is alumina.
[0017] In the present invention, the content of phosphorus oxide in the nickel-based catalyst is calculated based on the mass of elemental phosphorus (P).
[0018] According to some embodiments of the present invention, the aluminum oxide includes theta-alumina.
[0019] In the nickel-based catalyst provided by the present invention, if γ-alumina is used, its acidity is too strong, which easily causes styrene to polymerize and crosslink. α-alumina has very weak acidity, but its specific surface area is too small and the metal loading is low, resulting in insufficient catalyst activity. Therefore, it is more suitable to choose θ-alumina with lower acidity and higher specific surface area.
[0020] According to some embodiments of the present invention, the specific surface area of the nickel-based catalyst is 90 to 150 cm 2 / g, and the average pore size is 12 to 20 nm.
[0021] In a second aspect, the present invention provides a method for preparing a nickel-based catalyst, comprising:
[0022] S1 comprising a molybdenum precursor, a phosphorus and / or fluorine precursor, a lithium and / or potassium precursor solution, sesbania powder and alumina mixed, formed, dried for the first time, and calcined for the first time to obtain a support;
[0023] S2. impregnating the support with a solution comprising a nickel precursor, drying the support for a second time, and calcining the support for a second time to obtain the nickel-based catalyst.
[0024] The performance of the nickel-based catalyst provided by the present invention is closely related to the properties of the support. All elements other than nickel are added during support preparation. After heat treatment, a support with optimized acidity and suitable physical properties is obtained. The catalyst, using this support to support the nickel component, achieves a high phenylacetylene hydrogenation rate and extremely low styrene loss when applied to the selective hydrogenation of phenylacetylene from a styrene-rich C8 fraction.
[0025] According to some embodiments of the present invention, the aluminum oxide includes theta-alumina.
[0026] According to some embodiments of the present invention, the molybdenum precursor includes any one of ammonium molybdate and ammonium heptamolybdate.
[0027] According to some embodiments of the present invention, the phosphorus precursor includes phosphoric acid.
[0028] According to some embodiments of the present invention, the fluorine precursor includes ammonium fluoride.
[0029] According to some embodiments of the present invention, the lithium precursor includes lithium carbonate.
[0030] According to some embodiments of the invention, the potassium precursor comprises potassium carbonate.
[0031] According to some embodiments of the present invention, the nickel precursor includes nickel nitrate.
[0032] According to some embodiments of the present invention, the mass ratio of the nickel precursor calculated as nickel oxide, the molybdenum precursor calculated as molybdenum oxide, the lithium and / or potassium precursor calculated as metal oxides, the phosphorus and / or fluorine precursor calculated as elements of phosphorus and / or fluorine, and aluminum oxide is (10-30): (1-10): (0.5-5): (3-8): (47-85.5).
[0033] According to some embodiments of the present invention, the mass ratio of the sesbania powder to alumina is (0.008-0.046):1.
[0034] In the preparation method of the nickel-based catalyst provided by the present invention, the role of the sesbania powder is mainly to make the nickel-based catalyst easier to shape. It will decompose during the roasting process and will not become a component of the prepared nickel-based catalyst or affect the performance of the nickel-based catalyst.
[0035] According to some embodiments of the present invention, the temperature of the first drying is 100-120° C., and the time is 12-20 hours.
[0036] According to some embodiments of the present invention, the temperature of the first calcination is 400-600° C., and the time is 6-10 hours.
[0037] According to some embodiments of the present invention, the second drying is performed at a temperature of 100 to 140° C. for a time of 6 to 10 hours.
[0038] According to some embodiments of the present invention, the second calcination is performed at a temperature of 400 to 600° C. for 2 to 6 hours.
[0039] According to some embodiments of the present invention, the impregnation is performed at room temperature, and the impregnation time is 0.5 to 5.0 hours.
[0040] According to some embodiments of the present invention, the volume of the nickel nitrate solution is not less than the water absorption capacity of the carrier.
[0041] In a third aspect, the present invention provides a nickel-based catalyst prepared using the preparation method described in the second aspect.
[0042] In a fourth aspect, the present invention provides the use of the nickel-based catalyst described in the first aspect or the nickel-based catalyst described in the third aspect in selective hydrogenation, especially in the selective hydrogenation of phenylacetylene in a styrene-rich C8 fraction.
[0043] It should be noted that the styrene-rich fraction means that the content of styrene in the C8 fraction is much greater than the content of phenylacetylene.
[0044] The content of phenylacetylene in the C8 fraction of the present invention is 0.1-1.0%.
[0045] In a fifth aspect, the present invention provides a method for selective hydrogenation of phenylacetylene in a styrene-rich C8 fraction, comprising: first reducing the nickel-based catalyst described in the first aspect or the nickel-based catalyst described in the third aspect with hydrogen, then sulfurizing it with dimethyl disulfide to obtain a sulfurized nickel-based catalyst, and then using the sulfurized nickel-based catalyst for the selective hydrogenation reaction of phenylacetylene in a styrene-rich C8 fraction.
[0046] According to some embodiments of the present invention, the vulcanization temperature is 40-80°C.
[0047] According to some embodiments of the present invention, the conditions for hydrogen reduction are: hydrogen pressure of 0.2-0.5 MPa, hydrogen flow rate of 800-1200 mL / min, reduction temperature of 350-550° C., and reduction time of 12-24 h.
[0048] According to some embodiments of the present invention, the conditions for the selective hydrogenation reaction include: a reaction temperature of 20 to 50° C., a reaction pressure of 0.2 to 0.5 MPa, a molar ratio of hydrogen to phenylacetylene of (2 to 6): 1, and a raw material volume space velocity of 3 to 5 h -1 .
[0049] The beneficial effects of the present invention are at least:
[0050] The nickel-based catalyst provided by the present invention can be used as a selective hydrogenation catalyst. When used for the selective hydrogenation of phenylacetylene in a styrene-rich C8 fraction, it has good low-temperature activity, selectivity and stability, and has a high phenylacetylene hydrogenation rate and an extremely low styrene loss rate. DETAILED DESCRIPTION
[0051] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to illustrate this patent in detail and do not limit the scope of protection of the present invention in any way.
[0052] Unless otherwise defined, the technical terms used in the following examples have the same meanings as commonly understood by those skilled in the art to which this invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments, and equipment used in the following examples, etc., are all commercially available or can be obtained by existing methods; the reagent amounts used, unless otherwise specified, are the amounts used in conventional experimental procedures; and the experimental methods described, unless otherwise specified, are all conventional methods.
[0053] In the present invention, specific surface area and average pore size were measured using low-temperature nitrogen physical adsorption and desorption (BET) The specific method includes: using a US Digsorb-2600 automatic adsorption instrument, the sample is vacuum degassed at 400°C for 2 hours, and then the specific surface area of the sample is measured in liquid nitrogen using the krypton gas adsorption capacity method, and the results are calculated using the BET method.
[0054] Example 1
[0055] 1) Preparation of carrier:
[0056] 78.5 g of θ-alumina, 1.0 g of sesbania powder, 16.2 g of 60% ammonium heptamolybdate solution, 20 g of 50% phosphoric acid solution, and 8.67 g of 15% lithium carbonate solution were mixed and extruded into a clover-shaped body with a size of φ = 1.2 mm and a length of 2 to 15 mm to obtain a green body; the green body was dried at 120°C for 12 h and calcined at 400°C for 6 h to obtain the carrier Z1.
[0057] 2) Preparation of nickel-based catalyst:
[0058] The carrier Z1 was mixed with 64.2 g of a 40% nickel nitrate solution in multiple batches and impregnated at room temperature for 1 hour; the volume of the nickel nitrate solution was not less than the water absorption capacity of the carrier; the impregnated carrier was dried at 120°C for 8 hours and then calcined in air at 450°C for 4 hours to obtain a nickel-based catalyst C1.
[0059] The composition, specific surface area and average pore size of the nickel-based catalyst C1 are shown in Table 1.
[0060] Example 2
[0061] 1) Preparation of carrier:
[0062] 56g of θ-alumina, 0.5g of sesbania powder, 6.5g of 20% ammonium heptamolybdate solution, 20.3g of 70% phosphoric acid solution, 15g of 60% ammonium fluoride solution, 13.7g of 50% lithium carbonate solution, and 8.15g of 50% potassium carbonate solution were mixed and extruded into a clover shape with a size of φ = 1.2mm and a length of 2 to 15mm to obtain a green body; the green body was dried at 120°C for 12h and calcined at 600°C for 10h to obtain the carrier Z2.
[0063] 2) Preparation of nickel-based catalyst:
[0064] The carrier Z2 was mixed with 90.3 g of a 90% nickel nitrate solution in multiple batches and impregnated at room temperature for 2 hours; the volume of the nickel nitrate solution was not less than the water absorption capacity of the carrier; the impregnated carrier was dried at 120°C for 8 hours and then calcined in air at 600°C for 4 hours to obtain a nickel-based catalyst C2.
[0065] The composition, specific surface area and average pore size of the nickel-based catalyst C2 are shown in Table 1.
[0066] Example 3
[0067] 1) Preparation of carrier:
[0068] 65.5 g of θ-alumina, 3 g of sesbania powder, 19.4 g of 60% ammonium heptamolybdate solution, 26.8 g of 60% ammonium fluoride solution, and 5.52 g of 40% potassium carbonate solution were mixed and extruded into a clover shape with a size of φ = 1.2 mm and a length of 2 to 15 mm to obtain a green body; the green body was dried at 120°C for 15 h and calcined at 500°C for 8 h to obtain the carrier Z3.
[0069] 2) Preparation of nickel-based catalyst:
[0070] The carrier Z3 was mixed with 61.5 g of a 60% nickel nitrate solution in multiple batches and impregnated at room temperature for 3 hours; the volume of the nickel nitrate solution was not less than the water absorption capacity of the carrier; the impregnated carrier was dried at 120°C for 8 hours and then calcined in air at 450°C for 10 hours to obtain a nickel-based catalyst C3.
[0071] The composition, specific surface area and average pore size of the nickel-based catalyst C3 are shown in Table 1.
[0072] Example 4
[0073] 1) Preparation of carrier:
[0074] 60 g of θ-alumina, 2.5 g of sesbania powder, 14 g of 30% ammonium heptamolybdate solution, 36.1 g of 85% phosphoric acid solution, 15 g of 40% lithium carbonate solution, and 11.9 g of 30% potassium carbonate solution were mixed and extruded into a clover shape with a size of φ = 1.2 mm and a length of 2 to 15 mm to obtain a green body; the green body was dried at 120°C for 16 h and calcined at 600°C for 10 h to obtain the carrier Z4.
[0075] 2) Preparation of nickel-based catalyst:
[0076] The carrier Z4 was mixed with 92.5 g of an 80% nickel nitrate solution in multiple batches and impregnated at room temperature for 5 hours; the volume of the nickel nitrate solution was not less than the water absorption capacity of the carrier; the impregnated carrier was dried at 120°C for 8 hours and then calcined in air at 600°C for 4 hours to obtain a nickel-based catalyst C4.
[0077] The composition, specific surface area and average pore size of the nickel-based catalyst C4 are shown in Table 1.
[0078] Example 5
[0079] 1) Preparation of carrier:
[0080] 69 g of θ-alumina, 2 g of sesbania powder, 11.7 g of 50% ammonium heptamolybdate solution, 12.2 g of 50% ammonium fluoride solution, and 22.3 g of 20% potassium carbonate solution were mixed and extruded into a clover shape with a size of φ = 1.2 mm and a length of 2 to 15 mm to obtain a green body; the green body was dried at 120°C for 18 h and calcined at 550°C for 10 h to obtain the carrier Z5.
[0081] 2) Preparation of nickel-based catalyst:
[0082] The carrier Z5 was mixed with 70 g of a 70% nickel nitrate solution in multiple batches and impregnated at room temperature for 4 hours; the volume of the nickel nitrate solution was not less than the water absorption capacity of the carrier; the impregnated carrier was dried at 120°C for 8 hours and then calcined in air at 500°C for 4 hours to obtain a nickel-based catalyst C5.
[0083] The composition, specific surface area and average pore size of the nickel-based catalyst C5 are shown in Table 1.
[0084] Comparative Example 1
[0085] 1) Preparation of carrier:
[0086] 80 g of θ-alumina, 3.3 g of sesbania powder and water were mixed and extruded into a clover-shaped body with a size of φ=1.2 mm and a length of 2 to 15 mm to obtain a green body; the green body was dried at 120° C. for 18 h and calcined at 550° C. for 10 h to obtain a carrier D1.
[0087] 2) Preparation of nickel-based catalyst:
[0088] The carrier D1 was mixed with 70 g of a 70% nickel nitrate solution in multiple batches and impregnated at room temperature for 4 hours; the volume of the nickel nitrate solution was not less than the water absorption capacity of the carrier; the impregnated carrier was dried at 120°C for 8 hours and then calcined in air at 500°C for 4 hours to obtain the nickel-based catalyst CD1.
[0089] The composition, specific surface area and average pore size of the nickel-based catalyst CD1 are shown in Table 1.
[0090] Comparative Example 2
[0091] 1) Preparation of carrier:
[0092] 72 g of θ-alumina, 2.9 g of sesbania powder, 11.7 g of 50% ammonium heptamolybdate solution, and 22.3 g of 20% potassium carbonate solution were mixed and extruded into a clover-shaped body with a size of φ = 1.2 mm and a length of 2 to 15 mm to obtain a green body; the green body was dried at 120°C for 18 h and calcined at 550°C for 10 h to obtain the carrier D2.
[0093] 2) Preparation of nickel-based catalyst:
[0094] The carrier D2 was mixed with 70 g of a 70% nickel nitrate solution in multiple batches and impregnated at room temperature for 4 hours; the volume of the nickel nitrate solution was not less than the water absorption capacity of the carrier; the impregnated carrier was dried at 120°C for 8 hours and then calcined in air at 500°C for 4 hours to obtain the nickel-based catalyst CD2.
[0095] The composition, specific surface area and average pore size of the nickel-based catalyst CD2 are shown in Table 1.
[0096] Comparative Example 3
[0097] 1) Preparation of carrier:
[0098] 77 g of θ-alumina, 1.8 g of sesbania powder, and 12 g of 50% ammonium fluoride solution were mixed and extruded into a clover-shaped body with a size of φ = 1.2 mm and a length of 2 to 15 mm to obtain a green body; the green body was dried at 120° C. for 18 h and calcined at 550° C. for 10 h to obtain support D3.
[0099] 2) Preparation of nickel-based catalyst:
[0100] The carrier D3 was mixed with 70 g of a 70% nickel nitrate solution in multiple batches and impregnated at room temperature for 4 hours; the volume of the nickel nitrate solution was not less than the water absorption capacity of the carrier; the impregnated carrier was dried at 120°C for 8 hours and then calcined in air at 500°C for 4 hours to obtain the nickel-based catalyst CD3.
[0101] The composition, specific surface area and average pore size of the nickel-based catalyst CD3 are shown in Table 1.
[0102] Comparative Example 4
[0103] The difference from Example 5 is:
[0104] θ-alumina was replaced by α-alumina; the obtained carrier was recorded as D4; and the obtained nickel-based catalyst was recorded as CD4.
[0105] The composition, specific surface area and average pore size of the nickel-based catalyst CD4 are shown in Table 1.
[0106] Comparative Example 5
[0107] The difference from Example 5 is:
[0108] θ-alumina was replaced by γ-alumina; the obtained carrier was recorded as D5; and the obtained nickel-based catalyst was recorded as CD5.
[0109] The composition, specific surface area and average pore size of the nickel-based catalyst CD5 are shown in Table 1.
[0110] Comparative Example 6
[0111] The difference from Example 5 is:
[0112] 69 g of θ-alumina was replaced with 100 g of pseudo-boehmite (containing 69 wt% Al2O3); the obtained carrier was recorded as D6; and the obtained nickel-based catalyst was recorded as CD6.
[0113] The composition, specific surface area and average pore size of the nickel-based catalyst CD6 are shown in Table 1.
[0114] Comparative Example 7
[0115] 1) Preparation of carrier:
[0116] 69 g of θ-alumina, 2 g of sesbania powder, 12.2 g of 50% ammonium fluoride solution, and 22.3 g of 20% potassium carbonate solution were mixed and extruded into a clover-shaped body with a size of φ = 1.2 mm and a length of 2 to 15 mm to obtain a green body; the green body was dried at 120° C. for 18 h and calcined at 550° C. for 10 h to obtain the carrier D7.
[0117] 2) Preparation of nickel-based catalyst:
[0118] The carrier D7 was mixed with 11.7 g of a 50% ammonium heptamolybdate solution and 70 g of a 70% nickel nitrate solution in multiple batches and impregnated at room temperature for 4 hours; the volume of the nickel nitrate solution was not less than the water absorption capacity of the carrier; the impregnated carrier was dried at 120°C for 8 hours and then calcined in air at 500°C for 4 hours to obtain the nickel-based catalyst CD7.
[0119] The composition, specific surface area and average pore size of the nickel-based catalyst CD7 are shown in Table 1.
[0120] Table 1 Composition, specific surface area, average pore size of nickel-based catalysts of various embodiments and comparative examples
[0121]
[0122]
[0123] Application Example 1
[0124] Application of the catalysts obtained in the Examples and Comparative Examples in the selective hydrogenation of phenylacetylene in the C8 fraction:
[0125] 100 mL of each catalyst obtained in each example and comparative example was taken and reduced for 16 h under the conditions of a hydrogen pressure of 0.3 MPa, a temperature of 450° C. and a hydrogen flow rate of 1000 mL / min; then the temperature was lowered to 50° C., and under the conditions of maintaining the hydrogen flow rate and pressure, a cyclohexane solution of dimethyl disulfide (mass concentration of 0.044%, wherein the sulfur content was 300 ppm) was introduced for sulfurization for 15 h; at a temperature of 30° C., a reaction pressure of 0.3 MPa, a molar ratio of hydrogen to phenylacetylene of 4:1, and a raw material volume space velocity of 4 h -1 The C8 fraction feedstock was introduced under the conditions of for selective hydrogenation reaction. The mass percentage composition of the C8 fraction feedstock is shown in Table 2, and the hydrogenation results are shown in Table 3.
[0126] Table 2 Mass percentage composition of C8 fraction raw materials
[0127]
[0128]
[0129] Table 3 Selective hydrogenation reaction results of nickel-based catalysts of various examples and comparative examples
[0130]
[0131] As can be seen from Tables 1-3, the nickel-based catalyst of the present invention is used in the selective hydrogenation of phenylacetylene, which has a high phenylacetylene hydrogenation rate and an extremely low styrene loss rate. The outlet phenylacetylene content is not more than 5 ppm, and there is an increase in styrene. It can be used in the industrial production of trace phenylacetylene selective hydrogenation in the C8 fraction.
[0132] Comparative Application Example 1
[0133] The catalyst obtained in Example 5 was tested for the selective hydrogenation of phenylacetylene from a C8 fraction (the raw material composition by mass is shown in Table 2) using the same method as in Application Example 1, except that the procedure of cooling the mixture to 50°C, introducing a cyclohexane solution of dimethyl disulfide (0.044% by mass, containing 300 ppm sulfur) for 15 hours while maintaining the hydrogen flow rate and pressure was omitted. The hydrogenation results are shown in Table 4.
[0134] Application Comparative Example 2
[0135] The catalyst obtained in Example 5 was tested for selective hydrogenation of phenylacetylene from a C8 fraction (see Table 2 for the raw material mass percentage composition) using the same method as in Example 1, except that the sulfidation temperature was changed from 50°C to 100°C. The hydrogenation results are shown in Table 4.
[0136] Table 4 Selective hydrogenation reaction results of nickel-based catalyst in Example 5
[0137]
[0138] Catalyst stability evaluation
[0139] 100 ml of each catalyst from Example 5 and Comparative Example 3 were taken and the catalyst stability evaluation test was carried out using the same apparatus, raw materials, and reaction conditions as in Application Example 1. The results are shown in Table 5.
[0140] Table 5
[0141]
[0142]
[0143] It can be seen from Table 5 that the nickel-based catalyst of the present invention has good catalytic stability.
[0144] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation of the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein. On the contrary, the present invention can be extended to all other methods and applications with the same function.
Claims
1. A nickel-based catalyst, characterized in that The invention comprises a carrier and nickel oxide supported on the carrier, wherein the carrier comprises aluminum oxide, molybdenum oxide, at least one metal oxide of lithium and potassium, and at least one of phosphorus oxide and fluorine; The content of each component in the nickel-based catalyst is as follows: The balance is alumina.
2. The nickel-based catalyst according to claim 1, characterized in that The aluminum oxide includes θ-aluminum oxide.
3. The nickel-based catalyst according to claim 1 or 2, characterized in that The specific surface area of the nickel-based catalyst is 90 to 150 cm 2 / g, and the average pore size is 12 to 20 nm.
4. A method for preparing a nickel-based catalyst, characterized in that: include: S1 comprising a molybdenum precursor, a phosphorus and / or fluorine precursor, a lithium and / or potassium precursor solution, sesbania powder and alumina mixed, formed, dried for the first time, and calcined for the first time to obtain a support; S2. impregnating the support with a solution comprising a nickel precursor, drying the support for a second time, and calcining the support for a second time to obtain the nickel-based catalyst.
5. The preparation method according to claim 4, characterized in that The aluminum oxide includes θ-aluminum oxide; And / or, the molybdenum precursor includes any one of ammonium molybdate and ammonium heptamolybdate; and / or, the phosphorus precursor comprises phosphoric acid; and / or, the fluorine precursor comprises ammonium fluoride; and / or, the lithium precursor comprises lithium carbonate; and / or, the potassium precursor comprises potassium carbonate; And / or, the nickel precursor includes nickel nitrate.
6. The preparation method according to claim 4 or 5, characterized in that The mass ratio of the nickel precursor calculated as nickel oxide, the molybdenum precursor calculated as molybdenum oxide, the lithium and / or potassium precursor calculated as metal oxides, the phosphorus and / or fluorine precursor calculated as elemental phosphorus and / or fluorine, and aluminum oxide is (10-30): (1-10): (0.5-5): (3-8): (47-85.5).
7. The preparation method according to any one of claims 4 to 6, characterized in that The first drying temperature is 100-120°C and the time is 12-20 hours; And / or, the first calcination temperature is 400-600° C. and the time is 6-10 hours; And / or, the second drying temperature is 100-140° C. and the time is 6-10 h; And / or, the second calcination temperature is 400-600° C. and the time is 2-6 hours.
8. A nickel-based catalyst prepared by the preparation method according to any one of claims 4 to 7.
9. Use of the nickel-based catalyst according to any one of claims 1 to 3 or the nickel-based catalyst according to claim 8 in selective hydrogenation, especially in the selective hydrogenation of phenylacetylene in a styrene-rich C8 fraction.
10. A method for selective hydrogenation of phenylacetylene in a styrene-rich C8 fraction, characterized in that: include: The nickel-based catalyst according to any one of claims 1 to 3 or the nickel-based catalyst according to claim 8 is first reduced with hydrogen and then sulfurized with dimethyl disulfide to obtain a sulfurized nickel-based catalyst, and then the sulfurized nickel-based catalyst is used for the selective hydrogenation reaction of phenylacetylene in a styrene-rich C8 fraction; Preferably, the vulcanization temperature is 40-80°C.
Citation Information
Patent Citations
Selective hydrogenation method for phenylacetylene in the presence of phenylethylene
CN101475438A
Catalytic reduction of phenylacetylene in a styrene stream
CN1087892A
Process for the hydrogenation of phenyl acetylene in a styrene-containing medium with the aid of a catalyst
CN1298376A
Process for the selective hydrogenation of phenylacetylene
CN1852877A